COVID-19: spreading possibilities of human-animal-human and preventive measures - Prasannavenkatesan Theerthagiri; Vamsidhar Yendapalli (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - This paper reviews the possibilities of coronavirus disease 2019 (COVID-19) spreading from infected humans to pet animals and from pet animals to other animals and humans. Design/methodology/approach - A systematic literature review and meta-analysis were performed on research articles from November 2019 to August 2020. This study explored urgently needed research issues on COVID-19 infection spreading across animals and humans and vice versa. Findings - Essential and much needed precautionary measures and necessary preventive steps to protect pet animals from infection were highlighted. Originality/value - Essential investigation and experiment results were highlighted. The necessary measure to prevent the spread of infection among and across species and people was analyzed.